(untitled) (Universal International Scientific Journal, 2026)
JSC “Ammophos-Maxam” is well known for the production of ammophos fertilizers based on concentrated phosphorites. In the production process, extraction phosphoric acid (EPA) obtained by the dihydrate process is used as a raw material; its composition contains 18–19% phosphorus pentoxide (P2O5). The low P2O5 concentration in EPA significantly increases heat and energy consumption per unit of final product during the stages of evaporation, purification, and granulation in the production of high-phosphorus fertilizers. In the Republic, extensive efforts are currently being undertaken in this area. This article presents recent research results on the purification of dihydrate-process phosphoric acid from impurities carried out at JSC “Ammophos-Maxam”